منهجية القرآن في التعامل مع ظاهرة الاكتناز: دراسة تحليلية في أبعادها النفسية والتربوية والاجتماعية = The Qur’anic methodology in addressing the phenomenon of hoarding: an analytical study of its psychological, educational, and social dimensions - Elatrash, Radwan Jamal Yousef; Salhab, Belal Barakat Sulaiman (IIUM Press, 2026)
تُعالج هذه الدراسة موضوع منهجية القرآن في التعامل مع ظاهرة الاكتناز، وهي ظاهرة سلوكية متجذرة في النفس البشرية تقوم على جمع المال وتكديسه دون أداء حقوقه الشرعية أو إنفاقه في وجوه الخير. تتمثّل إشكالية البحث في أنّ الدراسات النفسية والاجتماعية الحديثة عالجت الاكتناز باعتباره اضطرابًا معرفيًا وسلوكيًا أو ظاهرة اجتماعية مؤثرة في العلاقات الأسرية، لكنها أغفلت الرؤية القرآنية التي تقدم علاجاً متكاملاً تجمع بين البعد النفسي والتربوي والاجتماعي. ومن هنا جاء هدف البحث متمثلًا في بيان منهجية القرآن الكريم في معالجة الاكتناز، واستنباط الأبعاد النفسية والتربوية والاجتماعية التي تبرز من خلال النصوص القرآنية ذات الصلة. اعتمد البحث على المنهج الاستقرائي من خلال جمع الآيات المتعلقة بالاكتناز واستقرائها في سياقاتها المختلفة، وعلى المنهج التحليلي الاستنباطي لتحليل النصوص واستخلاص الدلالات القرآنية، ثم استنباط أبعادها النفسية والتربوية والاجتماعية. وتوصل البحث إلى أنّ القرآن الكريم عالج الاكتناز من خلال تأصيل قيم الاعتدال والقناعة، والتحذير من نتائجه النفسية المتمثلة في القلق والاضطراب، والتربوية المتمثلة في غرس البخل والأنانية في الأجيال، والاجتماعية المتمثلة في تعميق الفجوة الطبقية وتعطيل حركة المال في المجتمع. كما يبرز القرآن أن العلاج يكمن في تزكية النفس بالإنفاق، وتحريك المال في دورة اقتصادية عادلة، وربط السلوك المادي بالمصير الأخروي. وقد أوصى البحث بضرورة الإفادة من منهج القرآن في بناء برامج تربوية معاصرة تعالج النزعة الاستهلاكية والادخارية السلبية، وتعزيز ثقافة العطاء والتكافل الاجتماعي، فضلًا عن توظيف هذه المنهجية في السياسات الاقتصادية والاجتماعية التي تستهدف العدالة والتنمية. إن الأثر الأبرز لهذه الدراسة يتمثل في تقديم رؤية قرآنية متكاملة تتجاوز الطرح النفسي والاجتماعي الجزئي في الدراسات الغربية، وتفتح آفاقًا جديدة لتفعيل النص القرآني في معالجة ظواهر سلوكية واقتصادية معاصرة. This study addresses the Qur’anic methodology in dealing with the phenomenon of hoarding, a behavioral tendency deeply rooted in human nature, characterized by the accumulation and storage of wealth without fulfilling its obligatory rights or spending it in charitable causes. The research problem lies in the fact that modern psychological and social studies have examined hoarding as a cognitive-behavioral disorder or as a social phenomenon affecting family relations, yet they have overlooked the Qur’anic perspective, which provides a comprehensive approach that integrates psychological, educational, and social dimensions. The aim of this study is to clarify the Qur’anic methodology in addressing hoarding and to derive the psychological, educational, and social dimensions highlighted in the relevant Qur’anic texts. The research employs the inductive method by collecting and examining verses related to hoarding in their various contexts, alongside the analytical–deductive method to interpret the texts, extract Qur’anic meanings, and deduce their psychological, educational, and social implications. The findings reveal that the Qur’an addresses hoarding by establishing values of moderation and contentment, warning against its psychological consequences such as anxiety and distress, its educational outcomes such as instilling miserliness and selfishness in future generations, and its social impacts such as deepening class divisions and disrupting the circulation of wealth in society. The Qur’an further emphasizes that the remedy lies in self-purification through spending, ensuring fair economic circulation, and linking material conduct to ultimate accountability in the Hereafter. The study recommends drawing on the Qur’anic methodology to develop contemporary educational programs that counteract consumerist and negative saving behaviors, promote a culture of generosity and social solidarity, and incorporate these principles into economic and social policies aimed at justice and development. The main contribution of this research lies in presenting a comprehensive Qur’anic vision that transcends the partial psychological and social approaches of Western studies and opens new horizons for activating the Qur’an in addressing contemporary behavioral and economic challenges.